Knowledge, attitudes, and practices of source municipal solid waste management in rural and urban communities of Chachoengsao province, Thailand - Thummikkaphong , Sureeporn; Kumsri, Sirinun; Singsook, Chanapon (Creative Science, 2026)
Municipal solid waste is generated in all human communities, and individual practices such as purchasing decisions, daily habits, and household municipal solid waste management practices directly influence its volume. In 2025, urban communities generated 32,532.92 tons of municipal solid waste annually, compared with 2,325.74 tons in rural communities. Although urban areas produce more municipal solid waste due to population density and consumption patterns, rural areas often lack effective municipal solid waste management systems. This study employed a comparative cross-sectional design to assess knowledge, attitudes, and household municipal solid waste management practices among residents in urban and rural communities. A total of 124 participants were recruited, with 62 individuals from each area. The sample size was calculated using Cohen’s effect size method with G*Power software. The inclusion criteria were individuals aged 18 years and above who were residing in Sanam Chai Khet District and Mueang Chachoengsao District, Chachoengsao Province. Data were collected using a structured questionnaire covering knowledge, attitudes, and municipal solid waste management practices. Descriptive statistics, including frequency, percentage, mean, and standard deviation, were used for analysis. The results showed that urban participants had a moderate level of knowledge (66.6%), while rural participants had a low level of knowledge (48.06%). Attitudes toward household municipal solid waste management were moderate in both groups, with mean scores of 2.95 ± 0.69 among urban residents and 2.60 ± 0.61 among rural residents. Regarding practices, urban participants demonstrated moderate household municipal solid waste management practices (2.89 ± 0.61), whereas rural residents showed inadequate practices (2.33 ± 0.71). These results highlight the necessity of focused interventions to promote acceptable home municipal solid waste management practices and increase understanding, especially in rural populations. In both urban and rural regions, bolstering community-based education and waste management initiatives may assist lower waste production and lessen environmental effects. GRAPHICAL ABSTRACT HIGHLIGHTS This study compares municipal solid waste management practices in urban and rural communities. Urban residents showed higher knowledge levels than rural residents. Attitudes toward household solid waste management were moderate in both settings.